Avaliação do potencial de microgeração em despacho econômico para atendimento aos requisitos de etiquetagem de edifícios - Cruz, Vinicius Rorato da [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The discussions about the energy rationalization are gaining more and more space on the everyday of engineers and other professionals in the field of energy. A greater focus is being tied to commercial buildings, because they are one of the biggest responsible for the high energetic expenditure according to the National Energetic Balance, especially by the use of air conditioners for the people’s thermal comfort. Such finding made INMETRO to develop a building labeling procedure through th National Program of Electric Energy Conservation in Buildings; by means of this systematic, the built areas are classified by levels that go from A(the best) to E(the worst), taking into account envelopment, illumination system and air conditioning. A bonus process based on water rationalization, use of renewable energy sources, cogeneration systems or technical innovations, allows the classification to be changed up to one level. A study made exactly on a commercial building, the building of Foundation for Technological and Scientific Development located inside of the College of Engineering of Guaratinguetá, sought to identify technical/economic alternatives for the building certification and appealed to the bonus based on water rationalization. The present study is based on analysis of deploying a cogeneration system formed by internal combustion engine and an absorption refrigeration system as bonus alternative, so that the costs are analyzed regarding energy consumption and use of the motor. With the calculations and results, the viability of the building to receive a bonus from INMETRO through its National Program for Energy Conservation in Buildings is studied and concluded from this study whether or not you can get a better level of energy efficiency for the building in question... (Complete abstract click electronic access below)

As discussões acerca da racionalização de energia vêm ganhando cada vez mais espaço no cotidiano de engenheiros e demais profissionais da área de energia. Um foco maior está sendo atrelado aos edifícios comerciais, por serem um dos grandes responsáveis pelo elevado consumo energético, principalmente pelo uso do ar condicionado para o conforto térmico das pessoas. Tal constatação levou o INMETRO a desenvolver um procedimento de etiquetagem para edificações através do Programa Nacional de Conservação de Energia Elétrica em Edifícios; por meio desta sistemática, classificam-se os ambientes construidos em níveis de A (melhor) a E (pior) considerando-se envoltória, sistema de iluminação e de condicionamento de ar. Um processo de bonificações baseadas em racionalização do uso de água, emprego de fontes renováveis de energia, de sistemas de cogeração ou inovações técnicas permite que a classificação seja alterada em até um nível. Um estudo realizado no edifício da Fundação para o Desenvolvimento Tecnológico e Científico, situado no campus da Faculdade de Engenharia de Guaratinguetá, buscou identificar alternativas técnico/econômicas para a certificação da edificação, sendo que se recorreu à bonificação baseada em racionalização do uso da água. O presente estudo é baseado na análise de implantação de um sistema de cogeração composto por motor de combustão interna e um sistema de refrigeração por absorção como alternativa de bonificação, sendo para tanto analisados os custos referentes ao consumo de energia elétrica e à utilização do motor. Diante dos resultados obtidos, a viabilidade de que o prédio seja bonificado pelo INMETRO através do seu Programa Nacional de Conservação de Energia Elétrica em Edifícios é avaliada e a partir desse estudo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Energia eletrica e calor - Cogeração; Refrigeração